Respons Pertumbuhan Tanaman Mentimun (Cucumis sativus ) terhadap Pemberian Unsur Hara Fermentasi Buah Pepaya (Carica papaya ) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Research on Growth Responses of Cucumber (Cucumis sativus) to Fermented Papaya (Carica papaya) nutrients was carried out at the Workshop of the Faculty of Science and Technology, University of PGRI Palembang, aimed at assessing the response to the application of organic nutrient concentrations of fermented papaya on height, stem diameter and number of leaves on the vegetative growth of cucumber plants for four weeks. The study used the RAL method, namely the provision of organic nutrients fermented papaya fruit with six different concentrations. The results of the research showed that there was a significant effect of treatment on the three observed cucumber plant growth parameters. The P5 treatment (500 ml/L) resulted in the highest average value of 55.4 cm plant height, 18.32 leaf number and 0.98 cm plant stem diameter, which were significantly different from other treatments.